Short‐term economic impacts of ecological restoration in estuarine and coastal environments: a case study of Lone Cabbage Reef. Issue 1 (7th July 2021) - Botta, Robert; Borsum, J. Scott; Camp, Edward V.; Court, Christa D.; Frederick, Peter
Abstract : Increasing demand for ecological restoration in the pursuit of long‐term persistence of resource benefits has resulted in the development of a "restoration economy" in the United States, which has provided opportunity for business growth associated with ecological sustainability. Nearly all the restoration monitoring and evaluation efforts focus on the ecological outcomes of restoration, although the social and economic outcomes have received far less attention. One type of economic outcome that is often overlooked includes short‐term economic impacts, which measure the market activity associated with the implementation of an ecological restoration project. This paper will provide an overview of how input–output analysis can be used as a method to quantify the short‐term economic impacts of ecological restoration projects. Using the Lone Cabbage Reef restoration project in Florida as a case study and IMPLAN regional economic modeling software, we found that the implementation phase of the project supported 44 full‐ time and part‐time jobs earning $1.01 million in labor income and generated $5.08 million in total industry output, including $3.02 million in total value added within the regional economy. These findings support the notion that short‐term economic impacts are an important component when evaluating ecological restoration projects and can provide stakeholders with immediate and tangible, albeit short‐term results.